Environmental Conditions and the Growth Patterns of Acacia melanoxylon in Highland Humid Forests in North Tinderet Forest Block (Kenya) - Kiptoo, Thomas K.; Ole Kiyiapi, James L.; Sang, Francis K.; Odhiambo, Kenneth O.; Wanjohi, Bernard (African Journal of Education,Science and Technology (AJEST), 2023)
Acacia species represent one of the most important alien invasive species in many forest ecosystems. The number of quantitative studies exploring their response to environmental heterogeneity is few, especially in tropical, equatorial forested habitats. Therefore, this study aimed to determine ecological conditions and growth patterns of Acacia melanoxylon in highland humid forests in North Tinderet Forest Block in Kenya. Three (3) transects measuring 500 m long each were established in each of the sampling sites invaded by A. melanoxylon where three plots of 10 m × 10 m sizes were systematically spaced at 235 m intervals. In each of the 10 m × 10 m sized plots, all tree species of diameter at breast height (DBH) > 1.3 m and height were measured and recorded. The abundance (ind/m) of plant species was calculated for each site. The study established differences in the DBH, height and abundance of acacia trees relative to environmental variables where the differences occurred mainly due to rainfall, humidity and wind, while altitude, slope, and elevation resulted in negative growth response. These findings suggest that the set of selected environmental variables affected the distribution and growth of A. melanoxylon. It is thus recommended that future studies on ecological conditions for the growth of A. melanoxylon should be conducted in a controlled environment through growth response measurements which were not possible under the current study due to the limitation of time and resources.